2017
DOI: 10.1097/cad.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro and in-vivo combined effect of ARQ 092, an AKT inhibitor, with ARQ 087, a FGFR inhibitor

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…For patients with advanced metastatic or recurrent endometrial cancer, treatment failure is still high due to the loss of opportunity for surgery. With the elucidation of molecular mechanisms in endometrial cancer, an increasing number of molecular targeted drugs are being tested for clinical application, and some have shown beneficial effects [ 3 , 4 ]. Therefore, the potential mechanisms in the development of endometrial cancer, especially those involved in tumour metastasis, have become the basis for the development of molecular targeted therapy for endometrial cancer, which is essential for the treatment of this type of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with advanced metastatic or recurrent endometrial cancer, treatment failure is still high due to the loss of opportunity for surgery. With the elucidation of molecular mechanisms in endometrial cancer, an increasing number of molecular targeted drugs are being tested for clinical application, and some have shown beneficial effects [ 3 , 4 ]. Therefore, the potential mechanisms in the development of endometrial cancer, especially those involved in tumour metastasis, have become the basis for the development of molecular targeted therapy for endometrial cancer, which is essential for the treatment of this type of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that cancers with high expression of FGFR mRNA and protein are more likely to respond to FGFR inhibitors (Goke et al, 2015b;Pearson et al, 2016;Weiss et al, 2010). In addition, we and others have shown that in preclinical models where FGFR inhibition does not block PI3K pathway activation, the combination of FGFR and AKT/PI3K/ mTOR inhibition resulted in increased cell death (Fumarola et al, 2017;Packer et al, 2017;Yu et al, 2017). However, despite preclinical efficacy, dual FGFR/PI3K inhibition is unlikely to be evaluated in clinical trials due to its combined toxicity (Hyman et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Deregulation of this pathway causes amplification and mutation of genes encoding PI3K and AKT. Targeting the PI3K/AKT pathway and its downstream targets like FOXO1 and GSK3 appears to be an attractive approach to treat cancers that are known to have aberrant AKT activation [49]. High levels of constitutive AKT has been associated with a short survival rate in cancer patients [50,51].…”
Section: Discussionmentioning
confidence: 99%